Antioxidant of the endosymbiotic dinoflagellate Symbiodinium sp. from the sea anemone Stichodactyla haddoni Saville-Kent - Soostani, B.S.; Zarei Darki, B.; Yousefzadi, M.; Ranjbar, M.Sh. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2025)
Marine dinoflagellates are potentially useful for many biomedical, toxicological and ecological applications. This study focuses on determining the antioxidant properties of Symbiodinium sp. isolated from the sea anemone Stichodactyla haddoni, collected from the Persian Gulf and the Gulf of Oman in 2018 and 2019, purified and cultured also in vitro. Antioxidant activity and total antioxidant activity were determined by two methods using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical and ferric-reducing antioxidant power (FRAP). The highest DPPH radical scavenging activity detected was 135.78 μg · mL-1 in the methanolic extract of Symbiodinium sp. from the winter Chabahar Bay sample using LC50. The FRAP method showed the maximum antioxidant activity (0.3 μg mL-1) in the methanolic extract at the concentration of 2 mg · mL-1 in the same sample. Cluster heatmap analysis showed that antioxidant activity was highly correlated with physicochemical factors (temperature and salinity) in the methanolic extract of Symbiodinium sp. Our results showed that the role of antioxidants and the types of ROS that are predominantly neutralized by peridinin and diatoxanthin should be more carefully studied, and we recommend using the electron spin resonance (ESR) spectroscopic method to determine the antioxidant properties of algae that contain these pigments.